Rat sawaddikan lae prachatippatai : naw tang khong pak prachaphon pue khayai prachatippatai sang khwam pen tum lae saksri khong prachachon ([s.n.])
Welfare state and democracy : the direction for the people's ovement to expand democracy, establishe social justice and dignity for the poor.